Relationship of Nutritional Adequacy Figures to Nutritional Status of Students of SMA Negeri 10 Surabaya During The Pandemic - Aida Verdy Kumala Yuniar; Trias Mahmudiono (Media Gizi Kesmas, 2022)
Background. Nutritional adequacy figures are the amount of nutrients obtained by the body to maintain a person's nutritional status adequately. During the pandemic, the fulfillment of nutritional needs becomes more difficult. Due to the movement restrictions imposed. Consequently, teenagers also prefer to meet their needs online, such as oerdering foods and beverages daily. Objective. This study analyzed  the relationship between nutritional adequacy figures and the nutritional status of high school students during the pandemic. Method. This was an analytical observational study conducted at SMA Negeri 10 Surabaya, with a total of 202 students aged between 15 and 17 years. Measurements of respondents' nutritional status, anthropometry, physical activity, nutritional intake, and nutritional adequacy figures obtained through the Harris Benedict formula adjusted to the physical activity and gender of each respondent. The hypothesis was analized statistically using the chi-square test. Results. The results of the nutritioal status revealed that 51 students had mild deficits, 43 students had moderate deficits, 26 had severe deficits, and 24 students did not experience any deficit in nutritional adequacy. Among obese students, 33 students had no deficit, 15 students had mild deficits, 9 students had moderate deficits, and one student had a severe deficit. Based There was a significant relationship between the nutritional status and nutritional adequacy figures of students with p-value=<0.001. Conclusion. There is a significant relationship between nutritional adequacy and the nutritional status of respondents during the pandemic.